HER2 експресија и EBV асоцираност кај гастричен карцином во корелација со клиничко-патолошките карактеристики - Огњеновиќ, Љубомир (Медицински факултет, УКИМ, Скопје, 2019)
Introduction: In recent years the incidence and rate of gastric cancer deaths have been declining, but nevertheless it is one of the leading causes of cancer-related deaths worldwide, especially in developing countries. It is associated with several risk factors, of particular importance, attributable to Helicobacter pylori infection, and more recently to Epstein-Bar virus (EBV) infection, which association with gastric carcinoma is still the subject of research. Gastric carcinoma shows the excessive expression of HER2 protein (HER2/neu, ErbB-2) which is a 185-kDa transmembrane receptor for tyrosine kinases, and according to some authors is related to the size of the tumor, serous invasion and metastases in the lymph nodes, as well as poor prognosis for a period of 10-year-survival. Since literature data on the prognostic significance of HER2 are considered to be the subject of examination, and due to the fact that individual patients develop resistance to the therapy with monoclonal antibody against HER2, the research in this field is considered to be current and necessary. Aim: The main aim of this study was identification of the immunoexpression of HER2 and EBV with gastric cancer and their correlation with certain clinical-pathological paramatres in order to determine their value as prognostic factors and to enrich the knowledge of the etiological and therapeutic characteristics of gastric carcinoma. Material and Methods: The study included 149 patients with gastric cancer, who underwent surgery at the University Clinic for Digestive Surgery in Skopje, and whose operative material was analyzed at the Institute of Pathology of the Medical Faculty in Skopje. In addition to demographic characteristics and intragastric carcinoma localization, the immunosuppression of HER2 and EBV in the tumor tissue was determined, and this was correlated with pathohistological and clinical parameters (tumor differentiation, local tumor growth, presence of metastases in the regional lymph nodes, presence of distant metastases and stage of the disease). Results: In this study, 41 (27.52%) male and 108 (72.48%) female patients were analyzed for the expression of HER2 protein in the tissue samples of gastric carcinoma. The age range of patients was from 40 to 86 years, with an average age of 65.19 ± 10.1 years. For EBV expression in this study tissue samples of 80 patients with gastric carcinoma were analyzed, of which 25 (31.25%) male and 55 (68.75%) female with age range from 40 to 86 years, with an average age of 65.19 ± 10.1 years. Regarding ethnicity, 114 (76.51%) patients were Macedonians, and 35 (23.49%) were of Albanian nationality. HER2 - positive staining in tumor tissue was found in 29.7% of patients. High degree of expression of HER2 or HER2 +++ scheme was significantly associated with GC localized in the anthro-pyloric region (p = 0.005) and with nodal metastases (p = 0.03). According to the differentiation of the tumors, positive HER2 expression was statistically significantly more common in moderately differentiated carcinomas in comparison to poorly differentiated carcinomas (p = 0.034), but the HER2 +++ scheme was significantly more frequent in patients with well differentiated carcinomas. EBV-associated gastric carcinoma was found in 23.7% of patients in the examined series with significantly higher frequency in patients of Albanian nationality (p = 0.009). EBV expression in gastric carcinoma was significantly more frequent in patients with distant metastases (p <0.0001). A highly significant correlation between HER2 positivity and EBV expression in gastric carcinoma (p = 0.041) was found, where HER2 expression was more common in the EBV negative gastric carcinoma (p = 0.02). Conclusion: The statistically significant difference in the expression of HER2 protein in patients with nodal metastases and the statistically significant negative correlation of HER2 expression with the tumor grade indicate that HER2 expression is significantly correlated with a more aggressive disease and the possibility of poor outcomes in patients with gastric carcinoma. In this study, a high percentage of EBV-associated gastric carcinoma was determined. The significant correlation of EBV immunoexpression with distant metastases in patients with GC suggests the impact of EBV infection on the progression of gastric carcinoma. Due to the relatively scarce and inconsistent literature on EBV-associated gastric carcinoma, additional studies are necessary in order to determine the role of EBV in relation to etiology, treatment and prognosis of patients with EBV-associated gastric cancer.
HER2 expression and EBV association with gastric carcinoma in correlation with clinical-pathological characteristics
Докторска дисертација одбранета во 2019 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Владо Јаневски.
Keywords: gastric carcinoma, HER2, EBV, prognostic factors, stage